The Impact of Exclusive Breastfeeding on the Occurrence of Diarrhea in Babies between the Ages of 6 and 12 Months in Purwakarta Regency, Indonesia - Febriana, Rositta (Archives of The Medicine and Case Reports, 2024)
Diarrhea is a prevalent infectious ailment among babies and young children. Exclusive breastfeeding decreases the occurrence of diarrhea. The objective of this study is to assess the efficacy of exclusive breastfeeding in reducing the occurrence of diarrhea among babies aged 6–12 months in Purwakarta Regency, Indonesia. This study employs an observational design utilizing a cross-sectional method. The research sample consisted of babies aged 6–12 months residing in Purwakarta Regency, Indonesia. We gathered data by utilizing a questionnaire. We used the chi-square test to analyze the data. The study's findings indicated a notable correlation between exclusive breastfeeding and the occurrence of diarrhea (p = 0.001). Babies who receive exclusive breast milk have a significantly reduced risk, 13.661 times lower, of developing diarrhea compared to babies who do not receive exclusive breast milk. In conclusion, exclusive breastfeeding is efficacious in avoiding diarrhea among babies aged 6–12 months.